Possibilities of using electronic payment instruments in the development of country payment systems - Narmamatov Bakhtiyarovich, Ikhtiyar (THE INNOVATION ECONOMY, 2024)
Creation of a unified information and legal environment in the field of payments and payment systems, effective regulation of the payment services market by the Central Bank, the functioning of payment systems, the activities of payment system operators and payment service providers, a number of practical works are being carried out to increase the popularity and transparency of payment services, as well as improving relations in the field of electronic money and the activities of participants in the electronic money system. It should be noted here that central bank digital currencies are fundamentally different from government-owned cryptocurrencies. The increased use of cryptocurrencies as a means of payment may reduce the demand for cash and the demand for funds in Nostro representative accounts of commercial banks with the Central Bank. However, the dangerous aspect of the circulation of cryptocurrencies is that their circulation is not controlled by central banks and the state. This could have a serious negative impact on the stability of cryptocurrencies. The article identifies current problems associated with ensuring the widespread implementation of modern payments and payment systems in the Republic of Uzbekistan, and develops scientific proposals for solving them.